A Meta-Analysis of Risk Markers for Intimate Partner Violence in Same-Sex Relationships. (July 2019) - Kimmes, Jonathan G.; Mallory, Allen B.; Spencer, Chelsea; Beck, Austin R.; Cafferky, Bryan; Stith, Sandra M.
Research on intimate partner violence (IPV) has largely focused on heterosexual relationships, but, in recent years, researchers have expanded their focus to include same-sex relationships. Using meta-analytic techniques, this study was conducted to examine the relative strength of various risk markers for men and women being perpetrators and victims of physical IPV in same-sex relationships. Articles were identified through research search engines and screened to identify articles fitting the inclusion criteria, a process that resulted in 24 studies and 114 effect sizes for the meta-analysis. The strongest risk marker among those with at least two effect sizes for both male and female perpetration was psychological abuse perpetration. The strongest risk marker among those with at least two effect sizes for IPV victimization was also perpetration of psychological abuse for males and psychological abuse victimization for females. Among same-sex-specific risk markers, internalized homophobia and fusion were the strongest predictors for being perpetrators of IPV for men and women, respectively. HIV status and internalized homophobia were the strongest risk markers for IPV victimization for men and women, respectively. Of 10 comparisons between men and women in risk markers for IPV perpetration and victimization, only 1 significant difference was found. The results suggest that although same-sex and heterosexual relationships may share a number of risk markers for IPV, there are risk markers for physical IPV unique to same-sex relationships. Further research and increased specificity in measurement are needed to better study and understand the influence of same-sex-specific risk markers for IPV.